2002
DOI: 10.1016/s0896-6273(02)01007-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Autophosphorylation of CaMKII Controls PSD Association, Plasticity, and Learning

Abstract: To investigate the function of the alpha calcium-calmodulin-dependent kinase II (alphaCaMKII) inhibitory autophosphorylation at threonines 305 and/or 306, we generated knockin mice that express alphaCaMKII that cannot undergo inhibitory phosphorylation. In addition, we generated mice that express the inhibited form of alphaCaMKII, which resembles the persistently phosphorylated kinase at these sites. Our data demonstrate that blocking inhibitory phosphorylation increases CaMKII in the postsynaptic density (PSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
319
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(351 citation statements)
references
References 44 publications
(3 reference statements)
28
319
0
Order By: Relevance
“…This description profile matches the inhibitory autophosphorylation that has been described for the alpha subunit of calcium/calmodulin-dependent kinase II (α-CaMKII) at Thr305 and Thr306, which lowers the affinity of CaMKII for CaM, and thus reduces Ca/CaM-mediated activation (27). β-CaMKII is expressed in Purkinje cells as well (28), but the inhibitory autophosphorylation has only been examined in α-CaMKII and has been shown to have a dominant negative effect on the holoenzyme (27). Both α-CaMKII and β-CaMKII are essential for proper LTD induction (28,29).…”
Section: Significancesupporting
confidence: 78%
See 1 more Smart Citation
“…This description profile matches the inhibitory autophosphorylation that has been described for the alpha subunit of calcium/calmodulin-dependent kinase II (α-CaMKII) at Thr305 and Thr306, which lowers the affinity of CaMKII for CaM, and thus reduces Ca/CaM-mediated activation (27). β-CaMKII is expressed in Purkinje cells as well (28), but the inhibitory autophosphorylation has only been examined in α-CaMKII and has been shown to have a dominant negative effect on the holoenzyme (27). Both α-CaMKII and β-CaMKII are essential for proper LTD induction (28,29).…”
Section: Significancesupporting
confidence: 78%
“…Negative regulation of CaMKII by Thr305/ 306 autophosphorylation requires prior calcium/calmodulin-mediated activation of CaMKII and subsequent calmodulin dissociation (31). Moreover, it has been shown that Thr305/306 phosphorylation, triggered by 10-Hz priming, reduces hippocampal LTP (32), whereas genetic manipulation of the Thr305/306 phosphorylation site lowers the LTP threshold and prevents priming (27,32). Thus, CaMKII inhibitory autophosphorylation depends on previous calcium signaling and directly affects the kinase/phosphatase balance, thus fulfilling the two requirements outlined above.…”
Section: Significancementioning
confidence: 99%
“…To test whether binding depended on the phosphorylation state of ␣CaMKII, we generated a double mutant (TT305/6VA) where two inhibitory autophosphorylation sites were removed. The threshold for kinase activation and for LTP induction is known to be lowered in the TT305/6VA mutant (21)(22)(23). Indeed, cells transfected with mutant ␣CaMKII had a significantly higher unrecoverable fraction of 42% Ϯ 28% (P Ͻ 0.05).…”
Section: Spine Volume Changes Induced By Pairing Of Glutamate Uncaginmentioning
confidence: 99%
“…Phosphorylation of these residues inhibits kinase binding to isolated PSDs (Strack et al, 1997b), α-actinin (Robison et al, 2005), and the NMDAR subunits NR1 and NR2B (Leonard et al, 2002). In addition, T305/6 phosphorylation increases the dissociation rate of CaMKII from the PSD (Shen et al, 2000), and mimicking phosphorylation on these residues prevents while inhibiting phosphorylation enhances PSD association of the kinase (Elgersma et al, 2002). Furthermore, CaMKII interaction with NR2B, which is enriched at the PSD, has been shown to suppress T305/6 phosphorylation (Bayer et al, 2001), and T306 phosphorylation leads to CaMKII dissociation from the synapse associated protein Camguk in Drosophila (Lu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%